2014
DOI: 10.1021/jp503416x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gas Species on Gas–Monolayer Interactions: Tangential Momentum Accommodation

Abstract: The tangential momentum accommodation coefficient (TMAC) of five gas speciesHe, N 2 , Ar, CO 2 , and SF 6 was measured on an octadecyltrichlorosilane-coated glass surfaces at 1.0 atm and 24 ± 2 °C. The TMAC was determined from measurement of the damping on a glass sphere near a glass plate when the separation between the sphere and plate was less than 1500 nm so that the flow was at or near the slip-flow regime. The results show that the damping depends on the gas species and that the fitted accommodation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Smaller TMAC has also been associated with heavier incoming molecules. Seo and Ducker found that SF 6 and CO 2 have smaller TMAC on octadecyltrichlorosilane-coated glass surfaces than He or N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Smaller TMAC has also been associated with heavier incoming molecules. Seo and Ducker found that SF 6 and CO 2 have smaller TMAC on octadecyltrichlorosilane-coated glass surfaces than He or N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…To find the coupling of the drift velocity to the rotation, we average the torque M over velocity space. Since the drift velocity is colinear with the heat flux, the last two terms in equation (20) can be combined to an effective torque such that…”
Section: B Thermophoresis and Orientation Of A Janus-spherementioning
confidence: 99%
“…In the context of the present work, only the surface properties of the two hemispheres are relevant. Two hemispheres with different momentum accommodation coefficients can be formed by varying the surface roughness [17,18] or by covering a part of the surface with a thin film [19,20]. While the motion of Janus particles in liquids have been widely discussed [21,22], little attention was given to the theoretical description of their transport in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is clear experimental evidence that special surfaces expose accommodation coefficients much smaller than 1. For example, values between 0.1 and 0.4 have been recently reported [30][31][32][33][34][35][36][37]. Therefore, the scenario considered in this paper is certainly not a standard case in terms of molecule-wall interactions, but refers to pumping principles that could become feasible with special tailor-made materials.…”
Section: Introductionmentioning
confidence: 99%